Strengthening of negative fire–fuel feedbacks by large fires in eastern Canadian boreal forests - Zackary Shakeri; Dominique Arseneault; Martin Simard; Marc-André Parisien (Proceedings of the National Academy of Sciences, 2026)
Fire-induced reductions in biomass limit the likelihood of reburning during early vegetation recovery in several crown-fire ecosystems; however, it is unclear how this negative fire–fuel feedback will buffer the rising fire activity expected with climate change. Although the feedback weakens with increasing time since the last fire and with increasing fire-weather severity, how the spatial configuration of fuel influences fire-return intervals remains unknown. Using a detailed 204-y fire history reconstruction along a 300-km longitudinal transect in eastern Canadian boreal forests, we show that interior areas of large fires (>8 km from the fire edge) are much less likely to reburn at short intervals than edges (<2 km from the edge), indicating a strengthening of the feedback within large burns. This process results in fewer fires in immature stands that are vulnerable to poor tree regeneration, thus conferring substantial resistance against compositional changes. However, the reduction in short-interval fires also fosters the development of large patches of mature forest that become extremely fire-prone after 4 to 5 decades and thereby predisposes landscapes to recurrent large fires. This study highlights an overlooked mechanism by which increases in fire size due to climate change may expose boreal forests of eastern Canada to large fires burning at longer intervals rather than to more frequent short-interval fires, which should sustain their capacity to recover.